Early phase clinical trials in pediatric oncology: Swedish pediatric oncologists’ experiences of balancing hope and expectations in life-threatening illnesses - Håkansson, Anna Schröder; Andersson, Ann-Christine; Abrahamsson, Jonas; Stenmarker, Margaretha (Frontiers in Oncology, 2024)
Aim: To study Swedish pediatric oncologists’ practical and emotional experiences of referring, including and/or treating children in early-phase clinical trials. Methods: A nationwide study was conducted using a mixed-method approach. Structured interviews based on a study-specific questionnaire and participants' personal reflections were utilized. Survey responses were analyzed using descriptive statistics, while participants' comments were analyzed using thematic analysis. All interviews were recorded and transcribed verbatim. Results: In total, 29 physicians with 4 to 32 years of experience in pediatric oncology participated, with 19 (66%) having > 10 years of experience. Three themes appeared: 1) Optimization-based approach focused on finding the most suitable treatment and care for every child with a refractory/relapsed cancer eligible for an early-phase clinical trial; 2) Team-based approach aimed at establishing local and national consensus in decision-making for treatment options, including early-phase clinical trials and palliative care; 3) Family-based approach in which the physicians provided families with actionable information, listened to their desires, and endeavored to maintain hope in challenging circumstances. Several participants (40% with ≤ 10 years of experience and 58% with > 10 years of experience) viewed the early-phase clinical trial as a potential “chance of cure”. A majority (80%) of physicians with ≤ 10 years of experience, reported that they often or always felt personally and emotionally affected by communication regarding early-phase clinical trials. Delivering difficult news in cases of uncertain prognosis was identified as the major challenge. None of the study participants felt adequately prepared in terms of sufficient knowledge and experience regarding early-phase clinical trials. The physicians expressed a need for guidance and training in communication to address these challenges. Conclusion: Working with early-phase clinical trials highlight a field where physicians cannot solely rely on their expertise or past experiences, and where they are likely to be deeply emotionally involved. Physicians who care for children eligible for such studies require targeted educational initiatives and supervision.